A formação de gabinetes no governo do estado do Espírito Santo (1995-2014) - Rocha, Rodrigo Taveira (2015)
This paper analyzes the cabinet formation in Espírito Santo’s Government in the period from 1995 to 2014. To do so, we start off from the debate on the Brazilian coalition presidentialism and its applications at sub-national level, reinforcing the importance of case studies and comparative studies. A rescue of the Espírito Santo’s policy trajectory is made, emphasizing the crisis period in the 1990s and institutional shift that occurred in the early 2000s. The composition of the legislative chamber of the state of Espírito Santo in the period is also highlighted, given its importance for the understanding of the relations between the Executive and Legislative powers. A database with all the Secretaries of State of the period was built, as well as their respective party affiliation, according to the Brazilian electoral court (TSE) data. Thus, one can compare the partisan composition of the cabinet and the size of the party caucuses in the legislative. For analysis of the offices’ proportionality this study uses the Coalescence Rate of Amorim Neto (2000) and the application of the Index G suggested by Avelino, Biderman and Silva (2011). In addition to the traditional usage of the party affiliation of the secretaries as a proxy for determining a political element in the cabinet, there is the proposition and parallel application of a new criterion that considers the party membership and the occurrence of previous application as indicative of a political secretary. The two criteria used show different results, and the fact that most of the formed offices were not majority suggests that in the Espírito Santo the distribution of positions in the first step of the government is not the main bargaining chip in agreements between executive and legislative.